Implementation of the fluorescent antibody technique neutralization virus test in rabies laboratory diagnosis of Pasteur institute of São Paulo / Brazil - Ferreira, J. S.; Trotti, A. C. P.; Scheffer, K. C.; Caporale, G. M. M.; Silva, A. C. R.; Chaves, L. B. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The Fluorescent Antibody Virus Neutralization Test (FAVN) is used routinely in many laboratories for the reference measurement of rabies virus neutralizing antibodies (VNA) in serum of animals to confirm the efficacy of vaccination against rabies, which is required to authorize the transit of these animals in countries free of rabies. The World Organization for Animal Health (OIE) recommends a VNA title ≥ 0,5 IU/mL to ensure that the animal has immunity against the rabies virus. The rabies laboratory diagnosis of Pasteur Institute of São Paulo/Brazil (IP/SP) is a national reference of the Ministry of Health for rabies diagnosis and performs the measurement of VNA in humans and animals serum samples for proof of immunization against rabies. The objective of this study was to implement the FAVN in the laboratory routine of rabies diagnosis at IP/SP using as reference the Rapid Fluorescent Focus Inhibition Test (RFFIT). Initially, the Challenge Virus Standard (CVS) was titrated by the FAVN and RFFIT methods, performing serial dilutions from 10-1 to 10- 12 and determining the dilution of 100 TCID50 (50% infectious dose in tissue culture) or 100 FFD50 (50% of the dose forming focus) for FAVN and RFFIT, respectively. A total of 97 serum samples from animals vaccinated against rabies with different ranges of VNA previously titrated by RFFIT, and 15 samples from unvaccinated animals were selected. Statistical analysis of agreement was performed considering the results in a qualitative analysis (< 0,5 and ³ 0,5) using the Kappa test. The CVS title was 10-6 in TCID50 for FAVN and 10-5 in FFD50 for RFFIT. The FAVN showed high specificity with titers <0,09 IU/mL and LogD50 <0,83 in samples from unvaccinated animals. Qualitative analysis of the results showed a substantial agreement between the two methods (kappa = 0,66, p <0,001). The titles of the sera from vaccinated animals were 0,12 IU/ml to 5,92 IU/ml (GM = 0.92 IU/mL) for FAVN and 0,13 IU/mL to 9,55 IU/mL (GM = 1,34 IU/mL) for RFFIT. The dilution factor in LogD50 values varied from 0,74 to 2,27 (GM = 1,55) for FAVN and 1,08 to 2,48 (GM = 1,84) for the RFFIT. The obtained results showed concordance within the parameters of specificity and sensitivity between FAVN and RFFIT methods. In this context, the implementation of FAVN in the rabies diagnosis laboratory IP/SP has a great importance for rabies epidemiological investigation by the VNA evaluation in animal serum samples and may complement the techniques already in use in the IP/SP.